Analysis of Students' Errors in Solving Mathematics Story Problems on Multiplication and Division - Sari, Dinda Permata; Riswari, Lovika Ardana; Santoso, Denni Agung (Jurnal Kiprah Pendidikan, 2025)
The background that forms the basis of this research is that some fourth-grade students of SDN 2 Dersalam Kudus still have difficulty in solving word problems related to multiplication and division. The problem in this research is the types of errors made by students when solving mathematical word problems related to multiplication and division. The aim of this research is to analyze and understand the types of errors that occur in fourth-grade students of SDN 2 Dersalam Kudus in solving word problems on multiplication and division. The method applied in this research is a descriptive qualitative approach, with the type of research in the form of a case study. The subjects in this research were three fourth-grade students of SDN 2 Dersalam Kudus in the 2024/2025 Academic Year. The data in this research were obtained through observation, interviews with teachers and students, and documentation. This study shows that students with high abilities do not make mistakes in solving story problems, while students with medium abilities make one type of mistake, and students with low abilities experience four types of mistakes in solving multiplication and division math story problems, so it is concluded that there are five types of mistakes that occur in students in the process of solving multiplication and division math story problems.